STANDAR NASIONAL PENGABDIAN KEPADA MASYARAKAT - Fatimah Dian Pertiwi (Jurnal Pengabdian Kepada Masyarakat, 2022)
Community service is actually not just a relaxing activity for lecturers or community learning activities for students of all universities, because in practice there are actually standards and need to be standardized nationally, so that there are minimal results achieved by students. Research activities and community service are the main tasks of lecturers listed in the Tri Dharma of Higher Education. The implementation must follow the applicable procedures and regulations. One of the rules is regarding the scope of research and national standards for community service. So that this national standard can apply to all lecturers in all Indonesian universities. The reference itself is also based on Article 1 of the Regulation of the Minister of Research, Technology and Higher Education of the Republic of Indonesia Number 44 of 2015 as well as the Regulation of the Minister of Education and Culture No. 3 of 2020 concerning National Higher Education Standards.